A Comparative Gender Analysis of Injury Characteristics, Treatments and Outcomes among Persons Seeking Emergency Care in Kigali, Rwanda - Lise Mumporeze; Chantal Uwamahoro; Doris Uwamahoro; Aly Beeman; Destry Jensen; Oliver Young Tang; Enyonam Odoom; Spandana Jarmale; Stephanie C. Garbern; Catalina González Marqués; Andrew Stephen; Adam R. Aluisio (Trauma Care, 2023)
In high-income nations, gender has been associated with injury characteristics. This study evaluated injury epidemiology and care based on gender at the Centre Hospitalier Universitaire de Kigali in Rwanda. Patients presenting to the emergency department with acute injuries were prospectively enrolled from 27 January–28 June 2020, and descriptive statistics were performed with comparisons between males and females. Of 601 patients, 25.6% were female and 74.4% were male. There were gender differences in the mechanism of injury, with females more likely to be injured in falls (43.5% versus 23.0%, p = 0.001); meanwhile, males were more likely to suffer road traffic accidents (52.6% versus 39.6%, p = 0.006). The severity of injury was similar between genders based on the mean Kampala Trauma Score (14.4 versus 14.7, p = 0.09). Females were more likely to have been transported by prehospital services (87.7% versus 72.9%, p = 0.001), and less likely to receive acute treatment during the first six hours of care (67.5% versus 78.1%, p = 0.009). There was no significant difference in mortality between females and males (2.0% versus 1.3%, p = 0.568). This study highlights differences in the epidemiology and care between males and females presenting for emergency injury care in Rwanda. These findings can inform future research and developments in gender-centered healthcare delivery.